2020
DOI: 10.1111/jen.12812
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic fungus isolates for adult Tuta absoluta (Lepidoptera: Gelechiidae) management and their compatibility with Tuta pheromone

Abstract: Tomato (Solanum lycopersicum Mill.) (Solanaceae) is one of the most widely cultivated and consumed Solanaceous vegetable crop in the world. It is a major source of nutritious food and socioeconomic driver, providing a means of livelihood for rural dwellers (Heuvelink, 2005; Wafula, Waceke, & Macharia, 2018). However, tomato production in Africa is seriously challenged by insect pests and diseases that cause significant yield loss. In Africa, yield losses generally varied and ranged from 11% to 43% but can reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…The pupae were collected from the plastic containers using a fine camel hair-brush and placed inside a clean plastic container for adult emergence. The colony was rejuvenated every three months through infusion, with infested tomato leaves collected from the field to reduce inbreeding 13,76 . All the treatments were arranged in a randomized complete block design and the experiment replicated four times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pupae were collected from the plastic containers using a fine camel hair-brush and placed inside a clean plastic container for adult emergence. The colony was rejuvenated every three months through infusion, with infested tomato leaves collected from the field to reduce inbreeding 13,76 . All the treatments were arranged in a randomized complete block design and the experiment replicated four times.…”
Section: Methodsmentioning
confidence: 99%
“…* email: kakutse@icipe.org control approaches using entomopathogenic fungi has shown promising results as they cause high mortality to insect pests of economic importance [9][10][11][12] . Akutse et al 13 reported the potential of fungal pathogens to control the pest and subsequently identified three Metarhizium anisopliae (Metschnikoff) Sorokin strains (ICIPE 18, ICIPE 20 and ICIPE 655) as candidate biopesticides causing mortality of 95.0, 87.5 and 86.25%, respectively against the adult stage of the pest. Entomopathogenic fungi have been traditionally used to control insect pests mostly through inundative application 14 .…”
mentioning
confidence: 99%
“…These results suggest that ICIPE 7 and ICIPE 621 could be used combined with S. frugiperda pheromone as an “attract and infect” strategy for sustainable management of the fall armyworm. Also, Akutse et al [ 166 ] observed high efficacy of M. anisopliae isolates ICIPE 18, ICIPE 20, and ICIPE 665 against both adult and fourth instar larvae of the tomato pest T. absoluta , when used in combination with the Tuta pheromone, TUA-Optima ® , for mass trapping and auto-dissemination. The results suggest them as promising and appropriate applicants as fungal-based biopesticides against T. absoluta and other solanaceous pests.…”
Section: Application Of Insect Sex Pheromonesmentioning
confidence: 99%
“…The experiment was repeated as described above, but this time using inoculated "donor" females and mixing them with clean/healthy "recipient" males. Mortality of both "donor" and "recipient" groups was recorded daily for ten days, including the controls according to procedures described in Akutse et al (2020) and Dimbi et al (2013). All the dead insects were examined for mycosis as described above in screening bioassay section.…”
Section: Horizontal Transmission Between Male and Female Trialeurodes Vaporariorum Adultsmentioning
confidence: 99%